Annual Report on Exchange Arrangements and Exchange Restrictions 1969. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1969)
This paper highlights the period under review was characterized by an unusually rapid increase in world trade and stresses on the international payments system. After a downturn in the rate of expansion of world trade in 1967, there was a sharp rise in the rate of growth in 1968. There was less emphasis on restrictions on current transactions, the main reliance being placed on capital controls in the efforts of the major trading countries to restore their balance of payments position. The area in which certain countries felt obliged to exercise control over current payments was the provision of exchange for travel expenditure, partly to prevent evasion of the capital controls. Several countries made important changes in their exchange and trade systems during the year tending toward liberalization of their restrictions. However, more restrictive import policies were adopted in other countries, which generally have a more important share in world trade.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet